SNI ISO/IEC 17025:2017 IMPLEMENTATION IMPACT ON TESTING LABORATORY - Andarwati, Sari; Brando, Robby Marlon; Mayasari, Ratna; Kristiningrum, Ellia; Agtusia, Arwidya Tantri (Badan Standardisasi Nasional, 2024)
A globally recognized standard for ensuring the competence of testing and calibration laboratories is SNI ISO/IEC 17025:2017. Many testing laboratories are currently using SNI ISO/IEC 17025:2017, and many have already received accreditation. The laboratory serves a variety of objectives, which is beneficial to enhancing the lab's performance. A laboratory's performance could be measured by how well it serves its customers and their satisfaction. This study aims to examine the impact of applying SNI ISO/IEC 17025:2017 on the number of services provided and the level of customer satisfaction in laboratories that have been accredited by KAN for the scope of CNC vertical-type milling machines and CNC lathes for position accuracy test, cutting result accuracy test, and circular movement accuracy test. This study uses a qualitative, descriptive research design and conducts elementary analysis to characterize the overall state of the data. Information on the number of services provided and the degree of customer satisfaction during 2016–2021 were compared, allowing for a comparison of the trends in service quantity and customer satisfaction. The findings indicate that the rise in laboratory services is influenced by the implementation of SNI ISO/IEC 17025:2017. Furthermore, as evidenced by a strong customer satisfaction score, the performance of the offered service has no bearing on the quantity of technological services falling under the purview of SNI ISO/IEC 17025:2017 accreditation.